2019
DOI: 10.11648/j.hep.20190401.14
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Factors Affecting Out-of-Pocket Medical Expenditure among Outpatients in ST.Paul Hospital Millennium College, Addis Ababa, Ethiopia

Abstract: The Objectives of the study is to assess the magnitude and factor that affect out-of pocket medical expenditure among outpatients department in St Paul's hospital Millennium College, Addis Ababa, Ethiopia. An Institution-based crosssectional study in quantitative method was conducted among outpatient services. The required sample size is determined by single population and double population proportion formula. The final sample size was 422. A descriptive statistical analysis, binary and multivariable logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…monthly diabetic care expenditure is 505 ETB (17.92 USD). It is lower than that of a study done on catastrophic health care expenditure in Ethiopia (610ETB) [24]. The possible explanation for this difference might be due to the fact that the previous study incorporated catastrophic health care expenditure as results of all diseases while the current study was conducted on catastrophic expenditure for diabetic care.…”
Section: Plos Onecontrasting
confidence: 57%
“…monthly diabetic care expenditure is 505 ETB (17.92 USD). It is lower than that of a study done on catastrophic health care expenditure in Ethiopia (610ETB) [24]. The possible explanation for this difference might be due to the fact that the previous study incorporated catastrophic health care expenditure as results of all diseases while the current study was conducted on catastrophic expenditure for diabetic care.…”
Section: Plos Onecontrasting
confidence: 57%
“…et.al (2018) [ 39 ] Amhara Cross-sectional 454 households 5 Low risk Fitsum S. et al (2018) [ 40 ] Amhara Cross-sectional 346 patients 8 Low risk Abyot A. et al (2018) [ 34 ] South Longitudinal 735 patients 7 Low risk Hailemichael Y. et.al (2019) [ 35 ] South Comparative cross-sectional 579 households 7 Low risk Hailemichael Y. et.al. (2019) [ 36 ] South Comparative ross-sectional 257 households 7 Low risk Biniam G. et al (2019) [ 37 ] South Cross-sectional 812 women 7 Low risk Amelewerk A. et al (2019) [ 46 ] Addis Ababa Cross-sectional 422 patients 7 Low risk Miljeteig I. et al (2019) [ 54 ] National Survey/ Cross-sectional 647 physicians 8 Low risk Obse AG. et.al.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled analysis of three studies revealed that marital status was associated with the burden of household Out-Of-Pocket / catastrophic healthcare expenditures (AOR 10.25, 95% CI: 0.92, 114.21) (Table 8 ). Marital status was associated total Out-Of-Pocket healthcare expenditures (AOR 0.20, 95%CI: 0.19, 0.20) [ 46 ]. However, being unmarried was found to be associated with higher median total cost (AOR 1.17, 95%CI: 0.02, 55.40) [ 40 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations